THE INTERTWINED LIVES: SCHIZOPHRENIA AND QUALITY OF LIFE - A SYSTEMATIC REVIEW - Petrova, Anya (Ayden Journal of Drug and Pharmaceutical Research, 2024)
Schizophrenia is a debilitating and complex syndrome that affects around 1% of the global population, ranking among the top ten most disabling diseases according to the World Health Organization. This chronic condition significantly impacts the quality of life for individuals afflicted by it, causing distress not only to the patients themselves but also to their families and caregivers. Typically, the initial signs and symptoms manifest between the ages of 20 and 25, often in the form of psychotic episodes. Schizophrenia is characterized by its variable course, which can be categorized into four stages: premorbid, prodromal, progression, and stabilization. The premorbid and prodromal phases precede the first episode of psychosis and are marked by low sociability, social anxiety, and cognitive impairments related to memory, attention, and performance. Following the first episode of psychosis, clinical presentation can be broadly categorized into three domains: negative, positive, and cognitive symptoms. Negative symptoms entail a range of emotional disturbances, including reduced affect, diminished pleasure in daily life, and difficulties in initiating activities. Positive symptoms manifest as psychotic behaviors, where patients struggle to differentiate between reality and hallucination. Cognitive symptoms, similar to negative symptoms, can be elusive but include reduced executive function, impaired information processing and decision-making, attention deficits, and memory problems.